Aspectos epidemiológicos e clínicos dos pacientes com fraturas por causas externas atendidos no Hospital de Clínicas de Uberlândia em 2003 - Ferreira, Diego Lelis (2006)
Introduction: between physical wounds caused by accidents and violence, the fractures take an evident place as they are common injuries, requiring long rehabilitation time for the victims to return to their daily activities and demanding an specialized hospital attend. Aim: to know epidemiological and clinical features of patients with fractures motivated by external causes in Uberlândia, MG. Material and method: it was done by collecting data from medical records from 1600 patients having fractures by external causes (accidents and violence), attended at Hospital de Clínicas de Uberlândia from January to December of 2003. Results: major of victims (1146; 71.6%) was attended at 09:00 a.m. to 09:00 p.m. period with quite homogeneity in the distribution of days of the week and months of the year, predominating the male ones (1090; 68.1%); 781 (48.8%) patients were at the range of 20 to 49 years old. From the whole, 1475 (92.2%) patients were victims of accidents, being falls (721; 48.9%) the most common, mainly the same level (484; 67.1%), and traffic accidents (553; 37.5%), mainly by motorcycle (279; 50.5%). On violence cases (125; 7.8%), predominated aggressions (113; 90.4%), mainly that using body strength (41; 36.3%). From the total of 2.063 episodes of bones/bones groups fractures, the most attained anatomical structures on accident cases (1910; 92.6%) were upper (841; 44.0%) and lower (686; 35.9%) limbs mainly with radius (309; 16.2%), femur (204; 10.7%) and tibia (177; 9.3%) fractures; on violence cases (153; 7.4%) were upper limbs (59; 38.6%) and cranium (58; 37.9%) mainly involving mandible (20; 13.1%), metacarpi(us) (18; 11.8%), nasal and ulna (14; 9.2% each). On majority of the 1600 cases (1166; 72.9%), only one bone was fractured. It was necessary 845 (52.8%) hospitalizations from which 610 (72.2%) patients stayed at the hospital until seven days. Among the 82 complication episodes directly related to fractures, verified in 79 (4.9%) patients, the most common were that related to synthesis material (40; 48.8%); 23 (1.4%) sequel cases occurred, with 14 (60.9%) amputations, and 35 (2.2%) obits, 26 (74.3%) of them occurred after 24 hours from injury, specially caused by falls (15; 57.7%). Conclusions: the people most attained by accidents and violence have between 20 and 39 years old and are male. They receive care most frequently from 09:00 a.m. to 03:00 p.m. of all days of the week and all months of the year. The accidents that most causes fractures are falls, especially that from the same level, and traffic accidents, mainly by motorcycle; between violence, the most common is aggression using body strength. Majority of cases, only one bone is fractured; between the accidents victims, the fractures occur mainly in upper and lower limbs involving especially radius and femur; among the violence victims, they occur in upper limbs and cranium, especially in mandible and metacarpi(us). Major of patients needs hospitalization and to stay at the hospital during a period of until a week. The complications are generally post-operative ones and related to synthesis materials. The most common sequels are amputations. The lethality is higher between fall victims.